Plant‐Based Structures as an Opportunity to Engineer Optical Functions in Next‐Generation Light Management. Issue 6 (18th December 2021) - Kaschuk, Joice Jaqueline; Al Haj, Yazan; Rojas, Orlando J.; Miettunen, Kati; Abitbol, Tiffany; Vapaavuori, Jaana
Abstract: This review addresses the reconstruction of structural plant components (cellulose, lignin, and hemicelluloses) into materials displaying advanced optical properties. The strategies to isolate the main building blocks are discussed, and the effects of fibrillation, fibril alignment, densification, self‐assembly, surface‐patterning, and compositing are presented considering their role in engineering optical performance. Then, key elements that enable lignocellulosic to be translated into materials that present optical functionality, such as transparency, haze, reflectance, UV‐blocking, luminescence, and structural colors, are described. Mapping the optical landscape that is accessible from lignocellulosics is shown as an essential step toward their utilization in smart devices. Advanced materials built from sustainable resources, including those obtained from industrial or agricultural side streams, demonstrate enormous promise in optoelectronics due to their potentially lower cost, while meeting or even exceeding current demands in performance. The requirements are summarized for the production and application of plant‐based optically functional materials in different smart material applications and the review is concluded with a perspective about this active field of knowledge. Abstract : This review presents a critical assessment of lignocellulosics for engineering optically functional materials for smart devices. It discusses the effects of fibrillation, fibril alignment, densification, self‐assembly, surface‐patterning, and compositing on targeted optical properties, such as transparency, haze, luminescence, UV‐absorption, and structural colors. The scope covers the main plant‐based structural materials, as well as non‐lignocellulosic additives bearing an optical function.